Anti-inflammatory effects of Nigella sativa in an Aspergillus niger Induced Rat Model of Otitis Externa - Mohammad Nurrizki Haitamy; Oke Kadarullah; Wulan Dyah Utami (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Otitis externa is an inflammatory condition of the external ear canal that can result from fungal infection, including Aspergillus niger. Nigella sativa (NS), known for its bioactive compounds, possesses notable anti-inflammatory and antioxidant properties. This study aimed to evaluate the anti-inflammatory effect of NS extract in an Aspergillus niger–induced rat model of otitis externa. Twenty-four rats were divided into four groups: Sham (healthy control), SW (A. niger–induced, untreated), T10 (treated with 20 mg/mL NS extract), and T20 (treated with 40 mg/mL NS extract). The inflammatory response was assessed histologically using hematoxylin and eosin (HE) staining, and quantitative analysis was performed by counting inflammatory cells infiltrating the external ear canal tissue. Administration of NS extract significantly reduced inflammatory cell infiltration compared with the SW group, demonstrating a dose-dependent anti-inflammatory effect. Histopathological examination revealed the lowest number of infiltrating inflammatory cells in the T20 group, followed by T10, while dense inflammatory accumulation was observed in the SW group. Quantitative analysis confirmed a statistically significant reduction in inflammatory cell count in both treatment groups compared with the SW group (p<0.05). These findings indicate that Nigella sativa extract effectively attenuates fungal-induced inflammation in the external ear canal